Cuidado de enfermería al paciente con COVID-19 en el centro de contingencia de la Ipress I-3 Pevas, Iquitos 2020 - Ramos Roque, Segundo Joel (2022)
The purpose of the work was to provide nursing care to patients with COVID-19 in a rapid response center using the Nursing Care Process; taxonomy II of the Nursing Diagnoses of the NANDA-NIC-NOC in the IPRESS 1-3 Pevas, the methodology used was descriptive and the case study design, 4 nursing diagnoses were identified: 00032: Ineffective respiratory pattern: R/C: Respiratory failure, Dyspnea and persistent cough, M/Decreased inspiratory/expiratory pressure. SPO2: 83%, RF: 26x'; 00198 Sleep pattern disorder R/C: Environmental and cultural factors; Lack of privacy and immobilization M/P: affliction and interrupted sleep, it is difficult for him to fall asleep due to an environment that is not typical of his Yagua ethnic group. 00146 anxiety R/C: Situational crisis, Interpersonal contagion; Stressful and cultural factors E/P: Out of fear, fear, grief in the face of COVID 19; (00004) Risk of infection R/C: Alteration of the integrity of the skin, decreased mobility, prolonged stay of the cannula in the respiratory tract. The care provided complied with the security protocols; the interventions of the health group contributed to the rehabilitation of the condescending woman of the Yagua ethnic group from her admission to her discharge; diagnosed with pneumonia due to COVID 19 and discharged with SpO2: 98%, P/A: 90/60 mgHg; Pulse: 68; RF: 20; TEMP: 36.7°.